Low-molecular Weight Heparins in Venous and Arterial Thrombotic Disease - Bijsterveld, Nick R.; Hettiarachchi, Rohan; Peters, Ron; Prins, Martin H.; Levi, Marcel; Büller, Harry R. (Thrombosis and Haemostasis, 1999)
Introduction: Since the introduction of low-molecular-weight heparins (LMWHs) in the early 1980's, the use of these compounds has been extensively investigated as a substitute for unfractionated heparin (UFH) in patients with venous and arterial thrombotic diseases. LMWHs have several advantages as compared to UFH, such as the subcutaneous route of administration, the predictable anticoagulant response and the lack of the need for laboratory monitoring. The present systematic review evaluates randomised clinical trials which investigated the efficacy and safety of LMWH in the acute treatment of venous thromboembolims, myocardial infarction, unstable coronary syndromes and ischemic stroke.Methods: A computerised and manual search was performed to identify all relevant clinical trials. All randomised studies, with an a priori defined study population, clinical outcome measurement and adequate follow-up, were reviewed by two independent assessors. Whenever possible a common effect estimate of the included studies was calculated.Results: Thirteen studies in approximately 4000 patients with acute venous thromboembolism revealed an odds ratio for the 3-month recurrent thromboembolism rate and major bleeding complications during exposure of 0.77 (C.I. 0.57-1.04) and 0.61 (C.I. 0.39-0.95), respectively, in favour of LMWH as compared to UFH. In patients with acute myocardial infarction, one study suggested a reduction in the incidence of reinfarction and cardiac death in LMWH recipients compared to UFH, while a placebo-controlled study revealed no beneficial effect of LMWH on these outcomes. In six studies including over 7000 patients with acute unstable coronary syndromes, there was an odds ratio for recurrent angina, myocardial infarction, urgent revascularisation and major bleedings of 0.88 (C.I. 0.76-1.01), 0.84 (C.I. 0.69-1.01), 0.83 (C.I. 0.70-0.99), 1.09 (C.I. 0.70-1.70), respectively, in favour of LMWH compared to UFH. The three studies comparing LMWH treatment with placebo in approximately 1000 patients with acute ischemic stroke revealed an odds ratio for the 10-day recurrent stroke, death or disability after 3 months and major bleeding complications of 0.68 (C.I. 0.41-1.13), 0.94 (C.I. 0.78-1.15), 2.92 (C.I. 1.88-4.55), respectively.Conclusion: Fixed-dose subcutaneous LMWH appears to be a safe and effective alternative for dose-adjusted intravenous heparin in the treatment of patients with acute venous thrombotic disease as well as in patients with acute unstable coronary syndromes. The effectiveness of LMWH in patients with acute myocardial infarction remains unclear. There seems to be no beneficial effect of LMWH treatment as compared to placebo in patients with acute ischemic stroke, while the risk of major bleeding was clearly increased.
Keywords: Venous thromboembolism; unstable coronary syndromes; cerebrovascular disorders; myocardial infarction; meta-analysis